Modified and Grafted Coronectomy: A New Technique and a Case Report with Two-Year Followup - Michael Leizerovitz; Olga Leizerovitz (Case Reports in Dentistry)
Purpose. A standard coronectomy (intentional partial odontectomy) is recommended for mandibular third molar (MTM) extraction cases with a high risk of inferior alveolar nerve injury (IANI). However, complications such as inadvertent intraoperative root removal, post-op root migration, second molar (MSM) periodontal defects and others do exist. This report presents a new technique, the Modified and Grafted Coronectomy (MGC), describes the measures to prevent or minimize the known drawbacks of the standard coronectomy, and reviews the literature for comparison with three other IANI-prevention techniques. Materials and Methods. MGC was performed on two MTMs with nerve involvement and severe periodontal pockets on the distal of MSM. Modifications were: stabilizing the root stump to prevent intraoperative movement, creation of a large intrabony space for bone graft material, and grafting for periodontal healing while minimizing the possibility of post-op root migration. Results. Excellent overall periodontal improvement, with probing depths reduced to 3-4 mm. Panoramic radiograph displayed remarkable bone regeneration. No residual root migration was evident at the two year follow up. Conclusion. MGC may be a good alternative, especially in cases with periodontal defects on the distal of MSM. It may also help to minimize inadvertent intraoperative root removal and postoperative root migration.